Genesis and cosmos Basil and Origen on Genesis 1 and cosmology - Rasmussen, Adam (Leiden Boston Brill, 2019)
Chapter 5 "Let them be for signs": Astrology1 Greco-Roman Astrology; 2 Origen; 3 Basil; 4 Interpretation and Analysis; Conclusion Basil and the Legacy of Origen; 1 Basil and the Anti-Origenist Movement; 2 Origen and Basil as Models for the Modern Science-Religion Debate; Bibliography; Index
Intro; Contents; Introduction Scripture and Science; Chapter 1 Origen, Basil, and Secular Education; 1 Origen of Alexandria; 2 Basil; 3 Conclusion; Chapter 2 The Interpretation of Scripture; 1 Origen; 2 Basil: Disciple of Origen; 3 Conclusion; Chapter 3 "The earth was invisible and unformed": Prime Matter and Creatio ex Nihilo; 1 Hylomorphism; 2 Pre-existent Matter and Creatio ex Nihilo before Origen; 3 Origen; 4 Basil; 5 Interpretation and Analysis; Chapter 4 "A separator between water and water": Cosmology and Water above the Sky; 1 Origen; 2 Basil; 3 Interpretation and Analysis
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Basil -- Saint, Bishop of Caesarea -- approximately 329-379; Origen -- Influence; Basil; Origen; Bible -- Criticism, interpretation, etc; Bible; Cosmology, Ancient; Cosmogony; Religion and science; RELIGION ; Christian Life ; Social Issues; RELIGION ; Christianity ; General; Influence (Literary, artistic, etc.); Criticism, interpretation, etc